2016
DOI: 10.3402/polar.v35.26133
|View full text |Cite
|
Sign up to set email alerts
|

Re-assessment of recent (2008–2013) surface mass balance over Dome Argus, Antarctica

Abstract: At Dome Argus, East Antarctica, the surface mass balance (SMB) from 2008 to 2013 was evaluated using 49 stakes installed across a 30)30 km area. Spatial analysis showed that at least 12 and 20 stakes are needed to obtain reliable estimates of SMB at local scales (a few hundred square metres) and regional scales (tens of square kilometres), respectively. The estimated annual mean SMB was 22.995.9 kg m (2 yr (1 , including a net loss by sublimation of (2.229 0.02 kg m (2 yr (1 and a mass gain by deposition of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
(36 reference statements)
2
19
0
Order By: Relevance
“…Precipitation and drifting snow sublimation were not considered in our calculations because of a lack of measurements. At Dome A, Ding et al () found a mass accumulation rate of 23 kg · m −2 · a −1 , and surface sublimation of 2.2 kg · m −2 · a −1 . The annual average wind speed at Panda‐1 Station is close to 10.5 m s −1 , whereas at Dome A Station it is less than 3 m s −1 .…”
Section: Discussionmentioning
confidence: 97%
“…Precipitation and drifting snow sublimation were not considered in our calculations because of a lack of measurements. At Dome A, Ding et al () found a mass accumulation rate of 23 kg · m −2 · a −1 , and surface sublimation of 2.2 kg · m −2 · a −1 . The annual average wind speed at Panda‐1 Station is close to 10.5 m s −1 , whereas at Dome A Station it is less than 3 m s −1 .…”
Section: Discussionmentioning
confidence: 97%
“…However, the 17 O‐excess values of the blowing snow should be lower due to the influence of kinetic fractionation at very low temperature (Angert et al, ; Pang et al, ; Risi et al, ), which cannot account for the observed high values of 17 O‐excess in summer precipitation at Dome A. Moreover, the wind speed at Dome A during summer is usually <3 m/s (Ding et al, ), which limits the blowing snow process. Therefore, we think that the blowing snow process should not be the reason for the observed lower δ 18 O values as well as high values of d‐excess and 17 O‐excess in summer precipitation at Dome A.…”
Section: Discussionmentioning
confidence: 99%
“…In the interior of Antarctica, summer months (December and January) are the warmest of the year and snow sublimation primarily occurs during the warmest season (Ding et al, 2016;Ekaykin et al, 2004;Frezzotti et al, 2004;Kameda et al, 1997). As a result, we focus our analysis on isotopic composition in summer precipitation and compare our data with results from surface snow at other sites of Antarctica (Masson-Delmotte et al, 2008) and nonsummer season precipitation (February to November) on the East Antarctic Plateau.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations